A view on absence. The filmic representation as a mirror of what man is not - Palacios, Víctor H. (2022)
Cinema is a privileged mean for exploring human condition, not only on that that is visible and effective following conventional realism. Fundamentally cinema reflects the human element in what it hides but at the same time shows powerfully. Its images may contain more than a mere reproduction of realities empirically verifiable, the unsubstitutable perspective of a personal view as well as the unholdable intensity of ‘truly’ presented dreams, horrors, illusions and all sort of afective elaborations, ludic and conceptual that compose the psichology and vital moment of an author. Man is also what it lacks in the visualization of these hard-to-hold deepnesess that will acquire a proper nature in other artistic means (word, mater, color).